A Drosophila model identifies calpains as modulators of the human leukemogenic fusion protein AML1-ETO. - Osman, D.; Gobert, V.; Ponthan, F.; Heidenreich, O.; Haenlin, M.; Waltzer, L. (Proceedings of the National Academy of Sciences of the United States of America, 2009)
The t(8:21)(q22;q22) translocation is 1 of the most common chromosomal abnormalities linked to acute myeloid leukemia (AML). AML1-ETO, the product of this translocation, fuses the N-terminal portion of the RUNX transcription factor AML1 (also known as RUNX1), including its DNA-binding domain, to the almost entire transcriptional corepressor ETO (also known as MTG8 or RUNX1T1). This fusion protein acts primarily by interfering with endogenous AML1 function during myeloid differentiation, although relatively few genes are known that participate with AML1-ETO during leukemia progression. Here, we assessed the consequences of expressing this chimera in Drosophila blood cells. Reminiscent of what is observed in AML, AML1-ETO specifically inhibited the differentiation of the blood cell lineage whose development depends on the RUNX factor Lozenge (LZ) and induced increased numbers of LZ(+) progenitors. Using an in vivo RNAi-based screen for suppressors of AML1-ETO, we identified calpainB as required for AML1-ETO-induced blood cell disorders in Drosophila. Remarkably, calpain inhibition triggered AML1-ETO degradation and impaired the clonogenic potential of the human t(8;21) leukemic blood cell line Kasumi-1. Therefore Drosophila provides a promising genetically tractable model to investigate the conserved basis of leukemogenesis and to open avenues in AML therapy.